2011
DOI: 10.1038/ajg.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Neoplastic Progression in Patients With Barrett's Esophagus: A Prospective Cohort Study

Abstract: In patients with BE, the risk of developing HGD or EAC is predominantly determined by the presence of LGD, a known duration of BE of ≥10 years, longer length of BE, and presence of esophagitis. One or combinations of these risk factors are able to identify patients with a low or high risk of neoplastic progression and could therefore be used to individualize surveillance intervals in BE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 43 publications
4
126
1
3
Order By: Relevance
“…In a retrospective study using the CORI (Clinical Outcomes Research Initiative) database, the yield of BE in white men with GERD was 2% in the third decade of life, but increased to 9% in the sixth decade ( 4 ). Early age ( 198 ) LGD to EAC 24 Studies, 2,694 patients 5.4/1,000 person-years 3-8…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study using the CORI (Clinical Outcomes Research Initiative) database, the yield of BE in white men with GERD was 2% in the third decade of life, but increased to 9% in the sixth decade ( 4 ). Early age ( 198 ) LGD to EAC 24 Studies, 2,694 patients 5.4/1,000 person-years 3-8…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Given the low rate of progression in these patients, the low but real rate of complications of endoscopic therapy ( 149 ), and the costs associated with its delivery ( 150 ), ablative therapy cannot be recommended in patients with nondysplastic BE. Whether these therapies are warranted in subjects judged to have a higher lifetime risk of cancer, such as those with familial BE/EAC and young patients with long segments of BE, is unclear (151)(152)(153).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In the studies performed on patients with GERD or any gastrointestinal system complaint in the countries to the west of Turkey, the prevalence of ERD varied from 10.2% to 50% (45,46). Moreover, in a study on patients having only dyspepsia in Brazil, the rate of ERD was found to be as low as 8.6% (47).…”
Section: The Epidemiology Of Gerd Complications In Turkey and Around mentioning
confidence: 99%
“…On the other hand, in a study conducted in Japan, the rate of patients that were endoscopically diagnosed with BE was reported to be 37.6%. However, a problem in this study arises from the fact that the authors defined the esophagogastric junction as the area where the esophageal palisade vessels ended (44).In the studies performed on patients with GERD or any gastrointestinal system complaint in the countries to the west of Turkey, the prevalence of ERD varied from 10.2% to 50% (45,46). Moreover, in a study on patients having only dyspepsia in Brazil, the rate of ERD was found to be as low as 8.6% (47).…”
mentioning
confidence: 99%
“…For this reason, it is essential that further risk stratification strategies will be developed to identify the subgroup of LGD patients who will benefit from ablative treatment in order to reduce unnecessary adverse events and costs in patients without a risk of neoplastic progression. It can be expected that the inclusion of additional risk factors for developing highgrade dysplasia and adenocarcinoma in BE, e.g., a known duration of BE of C10 years, longer length of BE, and presence of esophagitis [5], may help in risk stratification. Furthermore, it is recommended to ablate LGD only after revision by an expert pathologist and with two consecutive endoscopies confirming a diagnosis of LGD.…”
mentioning
confidence: 99%